Performance Analysis of NOMA and OMA in Terms of Throughput and User Capacity - Nidhi Chaudhary; N. P. Singh; Gaurav Verma (Exploration of Knowledge and Information in Sciences, Edition 1, 2025)
An increasing number of wireless devices in the present day putting a challenge of high spectral efficiency. The sixth generation (6G) is implemented to address this problem. But conventional orthogonal multiple access (OMA) approach is insufficient for the increased demand for spectrum. Non-orthogonal multiple access, or NOMA has drawn more and more interest in recent years from both academia and business and future 6G networks may find the NOMA technique to be advantageous as it offers spectrum efficiency, user fairness, better connectivity, and increased data rate, as compared to previous orthogonal multiple access approaches. Consequently, NOMA may be an appropriate multiple-access method due to its capacity to offer free random access and a further degree of flexibility for ultra-reliable low-latency communications (URLLC). This paper reviews the fundamentals of NOMA and related recent research on how beneficial it is in cooperative networks for improving performance analysis. The benefits of non-orthogonal multiple access (NOMA) have been well acknowledged in order to maximize the spectral efficiency. NOMA attracts many researchers as it solves the frequency deficiency problem by transmitting data at the same frequency and time. In NOMA data is transmitted in the power domain using Superposition coding at the transmitter side and successive interference cancellation at the receiver side. In this paper, we analyse the performance of NOMA in terms of received data rate (throughput) and ergodic capacity with the conventional OMA scheme.